2010
DOI: 10.1155/2010/570736
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Phenolic Glycoside from the Bark of Symplocos RacemosaRoxb

Abstract: A new phenolic glycoside, 3, 5 - dihydroxy - 2- (hydroxyl methyl) - 6-(3,4,5-trimethoxy phenoxy)tetrahydro-2H-pyran-4-yl, 4-hydroxy-3-methoxy benzoate have been isolated from the dried bark ofSymplocos racemosa. The structure was identified by extensive spectral analysis, especially FT-IR, GC-MS,1H NMR and13C NMR techniques. The method of isolation was simple, cost effective and efficient. The preliminary bioactivity of the compound was also evaluated. The ethanolic extract ofSymplocos racemosa(EESR) was inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Vijayabaskaran et al [36] also reported in vitro antioxidant potential of ethanolic bark extract of Symplocos racemosa Roxb.…”
Section: Resultsmentioning
confidence: 98%
“…Vijayabaskaran et al [36] also reported in vitro antioxidant potential of ethanolic bark extract of Symplocos racemosa Roxb.…”
Section: Resultsmentioning
confidence: 98%
“…is an evergreen tree which is commonly called as Lodhra is found in plains and lower hills throughout North and East India. It is reported to be used in the treatment of menorrhagia, other uterine disorders, inflammation, cleaning of uterus, liver and bowel complaints, tumors, asthma, fever, snake-bite and gonorrhea [5], [6], [7]. Composition and levels of bioactive compounds in plants vary with genetic factors, geographical origins, agricultural practices, harvesting and post harvesting processes, extraction processes etc.…”
Section: Introductionmentioning
confidence: 99%
“…Many species of this genus have been used as traditional herbal medicines for nephritis [19, 20]. The genus Symplocos mainly contains chemicals shown to have diverse biological activities, particularly anti-HIV activity, antitumor applications, antibacterial effects, and inhibitory activities against phosphodiesterase [21]. The compound 3 β -acetyloxy-oleanolic acid (AOA) was isolated from the root of Symplocos laurina Wall [22].…”
Section: Introductionmentioning
confidence: 99%